Keefektifan Metode Diskusi Dilema Moral Untuk Meningkatkan Penalaran Moral Peserta Didik Mamnu Ponorogo - Murdianto Murdianto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
Moral judgement is important for everybody, in the everyday life. In this study dilemma moral methods used to improve moral judgement in junior high scholl level in third class Madrasah Aliyah Maarif NU Ponorogo. This goal of research measures effectiveness of dilemma moral methods to improve student moral judgement. This study used experimental research with pretest-posttest control groupdesign. The 19 participants were divided into experimental group and control group. The experimental results were analyzed with Mann Whitney test and Wilcoxon test. Researcher used statistical software for experimental results analized with SPSS release 20.0 for windows. The research results showed that dilemma moral methods has effective to develop moral judgement of subjects.